Chebulagic acid suppresses gastric cancer by inhibiting the AURKA/β-catenin/Wnt pathway - Zhao, Jing; Shi, Yunfu; Ma, Yubo; Pan, Libin; Wang, Yanan; Yuan, Li; Dong, Jinyun; Ying, Jieer (Frontiers in Pharmacology, 2023)
Gastric cancer (GC) is a prevalent malignant neoplasm that poses a serious threat to human health. Overexpression of Aurora A (AURKA) is frequently associated with the self-renewal and tumorigenicity of various cancers. Chebulagic acid (CA) has been examined as a potential tumor suppressor based on its ability against numerous tumor biological activities. However, the possible mechanisms of CA inhibition of the progression of GC by mediating the AURKA/β-catenin/Wnt signaling pathway have not been investigated. The present study investigated the level of AURKA expression in GC. We further examined the effect of CA on cell proliferation, migration, and apoptosis in the MKN1 and NUGC3 GC cell lines, and its efficacy in suppressing tumor growth was assessed in tumor bearing mice model. We demonstrated that AURKA was highly expressed in GC and associated with poor prognosis. We demonstrated that treatment with CA significantly inhibited the proliferation and migration of GC cells and induced apoptosis. Compared to the vehicle group, CA treatment severely diminished the volume and weight and the metastasis of tumors. CA also inhibited the expression of AURKA and the AURKA/β-catenin/Wnt signaling pathway in vitro and in vivo. Collectively, the present results demonstrated that high expression of AURKA may be an independent factor of poor prognosis in patients with GC, and CA significantly suppressed the tumor biological functions of GC and inhibited the AURKA/β-catenin/Wnt pathway.